Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2672.1997.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus biomass as biosorbent for lead

Abstract: This paper deals with lead biosorption by Myxococcus xanthus biomass in which dry biomass, accumulating up to 1·28 mmol of lead g−1, is demonstrated to be a more efficient biosorbent than wet biomass. Dry biomass biosorption was found to be very rapid, reaching equilibrium after 5–10 min. Culture age, the initial lead concentration and pH affected this process, but temperature did not. Furthermore, by using sodium citrate as a desorbent agent, 92·17% of the biosorbed lead could be recovered. It was also establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…EPS provide an extensive surface area per unit volume for adsorption of heavy metal ions, such as Pb (Rudd et al 1984). This suggests 6 that the EPS could protect the bacterium in its habitat because these substances facilitate heavy metal fixation surrounding the cell rather than inside the cells (Merroun et al 1998). Merroun et al (2003) reported that Myxococcus xanthus, a soil bacterium of the myxobacteria group, could accumulate 0.6 mmol of La / g of wet biomass and/or 0.99 mmol / g of dry biomass, and a substantial amount of La was fixed in the EPS and in the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…EPS provide an extensive surface area per unit volume for adsorption of heavy metal ions, such as Pb (Rudd et al 1984). This suggests 6 that the EPS could protect the bacterium in its habitat because these substances facilitate heavy metal fixation surrounding the cell rather than inside the cells (Merroun et al 1998). Merroun et al (2003) reported that Myxococcus xanthus, a soil bacterium of the myxobacteria group, could accumulate 0.6 mmol of La / g of wet biomass and/or 0.99 mmol / g of dry biomass, and a substantial amount of La was fixed in the EPS and in the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Considering previous works from our laboratory which have indicated that dry biomass of M. xanthus removed more ef ciently heavy metals than wet biomass Ben Omar et al 1997;Merroun et al 1998), we decided to use dry biomass in these studies. Also, the age of cultures was chosen in agreement with our previous data.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our study on the recovery of heavy metals by M. xanthus it was found that dry biomass of this microorganism has the capacity to accumulate uranium and lead extremely well Merroun et al 1998). The similar behavior as was observed for the uptake of these two heavy metals was demonstrated here for silver: dry biomass of M. xanthus accumulates silver ions well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chromium and cadmium have been selected in this study because of their inherent toxicity to most organisms (Merroun et al,1998;Wan Ngah and Hanafiah, 2008). These metals are major pollutants in South Africa's water resources due to their use in many industries, such as metal plating, mining operations and tanneries.…”
Section: Introductionmentioning
confidence: 99%